Phytoseiid mites (Acari: Phytoseiidae) from Chile, with descriptions of three new species and a redescription of Chileseius camposi - Trincado, R. D.; Martin, J. P. I.; Rosa, D. D. Méndez; Lopes, P. C.; Moraes, G. J. De (Zootaxa, 2018)
A total of 40 phytoseiid species has been reported from Chile, including the two species (Neoseiulus californicus (McGregor) and Phytoseiulus persimilis (Athias-Henriot) most widely used worldwide for the biological control of the two-spotted spider mite, Tetranychus urticae Koch (Tetranychidae). In this paper we report nine other species found in new collecting conducted since 1989, including three new species: Amblyseius herbicolus (Chant), Amblyseius tamatavensis Blommers, Arrenoseius robertogonzalezi Trincado & Martin n. sp., Neoseiulus anonymus (Chant & Baker), Neoseiulus bicaudus (Wainstein), Neoseiulus viticolus Trincado & Martin n. sp., Metaseiulus (Metaseiulus) camelliae (Chant & Yoshida-Shaul), Metaseiulus (Metaseiulus) neoflumenis Moraes & Kreiter and Metaseiulus (Metaseiulus) relictus Trincado & Martin n. sp.. Chileseius camposi Gonzalez & Schuster, 1962 is redescribed, and a list of all species presently known from Chile and a key to help in their separation are given. A new name, Proprioseiopsis kargi Trincado nom. nov., is a replacement name for Proprioseiopsis globosus Karg, 1976, a junior homonym of Proprioseiopsis globosus (Gonzalez & Schuster, 1962).